Degradasi Penggunaan Bahasa Kaili sebagai Bahasa Ibu pada Masyarakat Tawaeli, Kota Palu - Syamsuddin, Syamsuddin; Putra, Rizky Anugrah; Mardiah, Mardiah (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Social and cultural changes today negatively impact the use of regional languages, particularly the Kaili language in Central Sulawesi, which is experiencing a decline in interest and usage among its community. This study aims to analyze the degradation of the Kaili language in the Tawaeli District of Palu, employing a qualitative descriptive method through surveys and interviews. The findings indicate that the Kaili language is increasingly infrequently used, especially among the younger generation, due to social factors such as community heterogeneity and a lack of usage within families. Additionally, the limited support from policies and local regulations for preserving the Kaili language presents a significant challenge. This research calls on all stakeholders to take concrete steps to promote the use of the Kaili language to ensure the continuity of the associated culture.